2009
DOI: 10.1016/j.jpowsour.2008.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Visualisation of water accumulation in the flow channels of PEMFC under various operating conditions

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractThe accumulation of water in the cathode/anode serpentine flow-channels of a transparent PEMFC has been investigated by direct visualisation where water droplets and slugs formed in these channels were quantified over a range of operating conditions. Four operating parameters concerning air stoichiometry, hydrogen stoichiometry, cell temperature, and electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 27 publications
(47 reference statements)
0
25
0
Order By: Relevance
“…Ous and Arcoumanis [107] found that flooding in the cathode channels can be overcome by raising the temperature from 30˚C to 60˚C under the testing conditions shown in Figure 2. The benefit of using heat as a mechanism for water extraction from the cell can be extended to the polarisation performance of the cell.…”
Section: Water Distribution and Transportmentioning
confidence: 98%
See 4 more Smart Citations
“…Ous and Arcoumanis [107] found that flooding in the cathode channels can be overcome by raising the temperature from 30˚C to 60˚C under the testing conditions shown in Figure 2. The benefit of using heat as a mechanism for water extraction from the cell can be extended to the polarisation performance of the cell.…”
Section: Water Distribution and Transportmentioning
confidence: 98%
“…Based on these design considerations, it is clear that unless the stoichiometric air flow is high water slugs will develop leading to flooding in the cathode channels [107]. It was shown by Ous and…”
Section: Water Distribution and Transportmentioning
confidence: 99%
See 3 more Smart Citations